2019
DOI: 10.1093/cid/ciz256
|View full text |Cite
|
Sign up to set email alerts
|

Dolutegravir-based Antiretroviral Therapy for Patients Coinfected With Tuberculosis and Human Immunodeficiency Virus: A Multicenter, Noncomparative, Open-label, Randomized Trial

Abstract: Background The concurrent treatment of tuberculosis and human immunodeficiency virus (HIV) is challenging, owing to drug interactions, overlapping toxicities, and immune reconstitution inflammatory syndrome (IRIS). The efficacy and safety of dolutegravir (DTG) were assessed in adults with HIV and drug-susceptible tuberculosis. Methods International Study of Patients with HIV on Rifampicin ING is a noncomparative, active-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 20 publications
3
86
0
2
Order By: Relevance
“…A total of 20 studies met the inclusion criteria to be included in the meta-analysis. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] The results include 5 studies for rilpivirine, [16][17][18][19][20] 14 studies for dolutegravir [21][22][23][24][25][26][27][28][29][30][31][32][33][34] and 1 study for dolutegravir/rilpivirine. 35 The total number of represented patients was 10 988 with the majority being male.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 20 studies met the inclusion criteria to be included in the meta-analysis. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] The results include 5 studies for rilpivirine, [16][17][18][19][20] 14 studies for dolutegravir [21][22][23][24][25][26][27][28][29][30][31][32][33][34] and 1 study for dolutegravir/rilpivirine. 35 The total number of represented patients was 10 988 with the majority being male.…”
Section: Resultsmentioning
confidence: 99%
“…In the ANRS 12,180 [37,38] and ANRS 12,300 [39,40] trials, RAL plus TDF/3TC was compared with EFV plus TDF/3TC. While in the INSPIRING [41,42] trial, DTG was compared with EFV plus major TDF/FTC, or plus other two N(t)RTIs. Drug doses of INIs (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…20,28 This has important implications for our findings, as dolutegravir will likely overcome the high levels of NNRTI resistance, has high barriers to resistance and can be co-administered with TB treatment. 29,30 However, the high prevalence of NRTI resistance (68% resistant to three or more NRTIs) suggest significant numbers could be on functional dolutegravir monotherapy. Data from the EARNEST trial demonstrated that even in the presence of predicted NRTI resistance, virological suppression with PI and NRTI based-regimens was good (89%).…”
Section: Discussionmentioning
confidence: 99%